The impact of psychological distance on judging satisfaction with nuclear energy policy via knowledge calibration and an integrated causal path model - Kim, Byoung Joon; Kim, Seoyong (Energies, 2021)
This study investigated how, through knowledge calibration and a causal path model, psychological distance can explain the level of satisfaction with nuclear energy policy. The investigation used multiple regression analysis and path analysis to explore relationships among variables. Data from 1056 adults revealed that more knowledge-calibrated individuals have more positive at-titudes toward nuclear energy policy. In addition, the psychological distance influences policy satisfaction by mediation of perceived risk of nuclear energy. This study aimed to increase the understanding of the dynamic of satisfaction with and acceptance of nuclear energy policy among stake-holders. Thus, based on the construal level theory, the study addressed the importance of knowledge and psychological distance in explaining variation in satisfaction and acceptance about nuclear policy.
Keywords: Construal levels; Level of satisfaction; Multiple regression analysis; Nuclear policy; Path analysis; Perceived risk; Psychological distance; Stake holders; Knowledge calibration; Nuclear energy policy; Policy satisfaction; Psychological distance; Risk perception